ARTISTIC INTERPRETATION OF THE IDEA OF NATIONAL REVIVAL IN NEW UZBEKISTAN LITERATURE (Universal International Scientific Journal, 2026)
This article analyzes the artistic interpretation of the idea of national awakening inearly 20th-century Uzbek Jadid literature. In the works of Jadid writers, issues such as enlightenment,the idea of independence, national self-awareness, and social reforms are examined from artistic andaesthetic perspectives. The research employs historical-comparative, typological, hermeneutic, andtextual analysis methods. In particular, the artistic expression of the concept of national awakening isrevealed through the works of Abdulla Avloniy, Abdurauf Fitrat, Mahmudxo‘ja Behbudiy, andCho‘lpon. The article provides a scholarly analysis of the ideological and artistic features of Jadidliterature and its role in the development of national consciousness
Keywords: Jadidism; national revival; enlightenment